2020
DOI: 10.1039/d0ra06618d
|View full text |Cite
|
Sign up to set email alerts
|

Interface engineering for gain perovskite photodetectors with extremely high external quantum efficiency

Abstract: Efficient CH3NH3PbI3 photodetectors (PDs) with an extremely high gain of the maximum external quantum efficiency (EQE) of 140 000% within the ultraviolet region to the near infrared region (NIR) and an extremely high responsivity (R) under a low bias of −5 V were successfully fabricated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Rui et al reported an EQE of 48,900% at −1 V by creating large density of trap states through tuning the composition of MAI vs PbI 2 of MAPbI 3 . In addition, other interfacial layers have also been used to further enhance the carrier trapping and to improve the gain by up to 140,000% using a MAPbI 3 perovskite active layer. Despite the high gain exhibited by hybrid perovskite photodiodes (PPDs) at a low-voltage operation, these materials pose severe constraints such as thermally unstable organic cations, unstable 3D crystal structure under ambient conditions, and lead toxicity . Therefore, as an alternative to lead halide perovskites, lead-free double perovskites (DPs) have been developed by replacing two Pb 2+ ions with pairs of cations with formal oxidation states +1 (Cu + , Ag + , and Au + ) and +3 (Bi 3+ , Sb 3+ , and In 3+ ) to preserve the average divalency.…”
Section: Introductionmentioning
confidence: 99%
“…Rui et al reported an EQE of 48,900% at −1 V by creating large density of trap states through tuning the composition of MAI vs PbI 2 of MAPbI 3 . In addition, other interfacial layers have also been used to further enhance the carrier trapping and to improve the gain by up to 140,000% using a MAPbI 3 perovskite active layer. Despite the high gain exhibited by hybrid perovskite photodiodes (PPDs) at a low-voltage operation, these materials pose severe constraints such as thermally unstable organic cations, unstable 3D crystal structure under ambient conditions, and lead toxicity . Therefore, as an alternative to lead halide perovskites, lead-free double perovskites (DPs) have been developed by replacing two Pb 2+ ions with pairs of cations with formal oxidation states +1 (Cu + , Ag + , and Au + ) and +3 (Bi 3+ , Sb 3+ , and In 3+ ) to preserve the average divalency.…”
Section: Introductionmentioning
confidence: 99%
“…Organic-inorganic hybrid perovskite has attracted much attention because of its low exciton binding energy, high absorption coefficient, wide spectral range, and long exciton diffusion length. It is a potential candidate material for next-generation photovoltaic devices [1][2][3][4][5][6]. Organic-inorganic hybrid lead halide perovskite solar cells (PSCs) have the characteristics of good solution processability, low cost, and high energy conversion efficiency [7,8] whicd considered to be a new generation of photovoltaic technology [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Photodetectors (PDs), which can detect irradiation directly by transforming light signals into electrical signals, have attracted much attention in the past decades due to their wide applications in versatile fields including environmental monitoring, space exploration, light communication, chemical and biological analysis, imaging etc. 1–6 Among these PDs, self-powered PDs have shown great potentials as they are effective, reliable and most importantly energy-saving. Differing from many PDs which can only operate under an external power source, self-powered PDs can work under zero bias by exploiting the photovoltaic effect from p–n junctions, heterojunctions or Schottky junction under light illumination.…”
Section: Introductionmentioning
confidence: 99%